MANAJEMEN ZAKAT SEBAGAI PENYEIMBANG PEREKONOMIAN UMAT - Raja Hesti Hafriza; Firdaus M.H; Ahmad Chuzairi (PERADA, 2018)
Zakah is one of the alternative solutions to reduce poverty. Besides being a pillar of Islam, zakah is able to resolve the social problems of Muslim society. The social condition of society today is still in the poverty line. So many people live with shortages. Therefore, zakah can solve the problem if it is implemented in a good management. From several related studies, the researcher tried to reconstruct some ideas that were spread. The results of this study indicates that Islamic management patterns are very different with conventional management. So that Islamic management must be a standard in the practice of zakah management carried out by zakah management organization. They should be conducted with the principles of faith, leadership, management and good administration. With Islamic management standards, zakat will be able to be collected, managed, utilized and distributed based on the conditions of Islamic law.